Avaliação do comportamento mecânico da reconstrução radicular em raízes enfraquecidas utilizando o método dos elementos finos - Claudia Machado de Almeida Mattos (2012)
The restoration of endodontically treated teeth is often a complex task, because of the great loss of coronal structure. When the destruction reaches the root, the flared canal makes the insertion of an endodontic post very difficult, during the prosthetic rehabilitation of the tooth. The reconstruction of the cervical root walls with adhesive restorative materials has been suggested, due to their favorable mechanical properties and dentin bonding ability. This study aimed to apply the finite element method to: (a) compare the stress distribution in endodontically treated teeth with reconstructed roots to those with healthy roots, under static loads; (b) investigate the location and probable modes of failure (root fracture, post dislodgement) of the reconstructed roots, according to the strength of the dentin and the materials used; (c) verify the behavior of these teeth under cyclic loads, based on the stress magnitudes and distributions, and also, based on the fatigue strength of the simulated materials; (d) compare the results to the data available in the literature. The software Ansys¥ 12.0 (Canonsburg, PA, EUA) was used for modeling and processing. Three geometric 3D models were created, representing a maxillary central incisor with a healthy root, post/core and crown restored (Model 1), or with weakened roots reconstructed with composite resin (Modelo2) or cermet glass ionomer cement (Model 3) prior to the post/core/crown restoration. A 100N load was applied on the palatal surface at 130o to the long axis of the tooth. The principal stresses (S1 and S3) were used for the stress analysis of the tooth, isolated root, post, cement and root reconstruction area. Under static loads, the results indicated that failure is unlikely to occur in the root dentin. However, there is a possibility of failure of the adhesive interfaces. In Model 2, the most probable failure would appear along the cement/dentin bonding interface, while in Model 3, this would happen along the dentin/ionomer interface. When compared to Model 3, the behavior of Model 2 is more similar to that of Model 1. Based on the fatigue strength of the materials that were simulated, the results demonstrate that, for the 3 models, the teeth work very close to the fatigue limit of the dentin. The results indicate an unfavorable prognosis for the adhesively reconstructed thin-walled roots. Therefore this treatment modality should be carefully indicated, taking into account the individual features of the patient.